Introducing the MeVCube concept: a CubeSat for MeV observations. Issue 8 (1st August 2022) - Lucchetta, Giulio; Ackermann, Markus; Berge, David; Bühler, Rolf
Abstract: Despite the impressive progress achieved both by X-ray and gamma-ray observatories in the last few decades, the energy range between ∼ 200 keV and ∼ 50 MeV remains poorly explored. COMPTEL, on-board the Compton Gamma-Ray Observatory ( CGRO, 1991-2000), opened the MeV gamma-ray band as a new window to astronomy, performing the first all-sky survey in the energy range from 0.75 to 30 MeV. More than 20 years after the de-orbit of CGRO, no successor mission is yet operating. Over the past years many concepts have been proposed, for new observatories exploring different configurations and imaging techniques; a selection of the most recent ones includes AMEGO, ETCC, GECCO and COSI . We propose here a novel concept for a Compton telescope based on the CubeSat standard, named MeVCube, with the advantages of small cost and relatively short development time. The scientific payload is based on two layers of pixelated Cadmium-Zinc-Telluride (CdZnTe) detectors, coupled with low-power read-out electronics (ASIC, VATA450.3). The performance of the read-out electronics and CdZnTe custom designed detectors have been measured extensively at DESY [1]. The performance of the telescope is accessed through simulations: despite a small effective area limited to a few cm 2, MeVCube can reach an angular resolution of 1.5° and a sensitivity comparable to the one achieved by the last generation of large-scale satellites like COMPTEL and INTEGRAL . Combined with a large field-of-view and a moderate cost, MeVCube can be a powerful instrument for transient observations and searches of electromagnetic counterparts of gravitational wave events.